2020
DOI: 10.1007/s10620-020-06535-5
|View full text |Cite
|
Sign up to set email alerts
|

Volume–Function Analysis (LiMAx Test) in Patients with HCC and Cirrhosis Undergoing TACE—A Feasibility Study

Abstract: Background Transarterial chemoembolization (TACE) is an important therapy for hepatocellular carcinoma (HCC) in cirrhosis. In particular in advanced cirrhosis, post-TACE hepatic failure liver (PTHF) failure may develop. Currently, there is no standardization for the periinterventional risk assessment. The liver maximum capacity (LiMAx) test assesses the functional liver capacity, but has not been investigated in this setting. Aims The aim of this study was to prospectively evaluate periinterventional LiMAx and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Recently, LiMAx ® was also investigated as an additional tool for patient selection prior to transjugular intrahepatic portosystemic shunt implantation [ 28 ]. In HCC patients, LiMAx ® has shown promising results in assessing liver function after TACE and was more accurate than the Child–Pugh score [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, LiMAx ® was also investigated as an additional tool for patient selection prior to transjugular intrahepatic portosystemic shunt implantation [ 28 ]. In HCC patients, LiMAx ® has shown promising results in assessing liver function after TACE and was more accurate than the Child–Pugh score [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were derived from a prospective study, where LiMAx ® was evaluated as an additional tool to predict the risk of hepatic failure caused by TACE. The authors reported that lower LiMAx ® values at baseline (<150 µg/kg/h) were associated with a significant increase in serum bilirubin levels after TACE [ 12 ]. This shows that the LiMAx ® measurement could predict even a minor deterioration in liver function due to locoregional therapy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, an adequate selection of patients suitable for a certain intervention is of fundamental importance. The LiMAx test was able to estimate prognosis with regard to liver surgery, transjugular intrahepatic portosystemic shunt (TIPS) or liver cancer therapies such as transarterial chemotherapy (TACE) or selective intra-arterial radiotherapy (SIRT; unpublished data) and decline from patients who will not benefit from these procedures [ 83 , 96 , 97 , 98 , 99 , 100 , 101 ]. However, it is not only possible to individually decide whether a certain intervention is possible but also to determine an appropriate timepoint.…”
mentioning
confidence: 99%
“…Current investigations could demonstrate reliable and reproducible results for LiMAx measurements in detecting changes in liver function, even with regard to modulations caused by superselective procedures. Enzymatic liver function measured by the LiMAx test was superior to biochemical parameters and conventional scoring systems such as CPS or ALBI score, which were less specific in providing sufficient information on cellular dysfunction [18,19] . In conclusion, various modalities for the treatment of patients with HCC have become available over the last decades.…”
mentioning
confidence: 99%